Pendaftaran Tanah Sistematis Lengkap Tanah tanpa Sertifikat sebagai Upaya untuk Mempercepat Reforma Agraria di Wilayah Kantor Pertanahan Kabupaten Tapin - Hiza, Ahmad Humaidul; Gozali, Djoni Sumardi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
To achieve nationwide land registration in Indonesia, despite regulatory support, systematic challenges persist in expediting the process known as Complete Systematic Land Registration (PTSL). These hurdles may impede the fulfillment of the mandate outlined in Article 19(1) of Law No. 5 of 1960. The research conducted is of a normative legal nature, focusing on legal norms, aligning with Peter Mahmud Marzuki's definition of legal research as inherently normative. The findings on Complete Systematic Land Registration in the Tapin Regency Land Office Area indicate that unregistered land owners face uncertainty and lack legal protection until their land is officially registered. Although Indonesia's land registration publication system allows for objections or lawsuits, legal certainty and protection are only guaranteed post-registration. The government aims to enhance certainty and protection through the PTSL program, emphasizing the importance of land certificates. However, despite serving as legal evidence of ownership, these certificates are not absolute in legal proceedings and can be subject to civil, criminal, or administrative challenges due to Indonesia's adversarial land registration system.